Wild Card: Stone Barrington #49 - Woods, Stuart; Roberts, Tony, 1939- (New York, NY : Penguin Audio, 2019)
A peaceful country retreat with his latest paramour is interrupted by an unknown, ruthlessly vengeful adversary who orchestrates multiple plots targeting Manhattan rainmaker Stone Barrington and his associates.
Read by Tony Roberts.
Keywords: Barrington, Stone -- (Fictitious character) -- Fiction; Private investigators -- Fiction; Suspense fiction; Adventure fiction; Audiobooks